Evaluation of Nurses’ Knowledge about Chest Physiotherapy Techniques for Patients with COVID-19 - Yassen, Ahmed; Ahmed, Sabah Abbas (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The present study aims to evaluate nurses’ knowledge about chest physiotherapy techniques for patients with coronavirus and to find out the relationship between nurses’ knowledge and their demographic characteristics. Methodology: A descriptive study was conducted at the isolation units in Al- Hussein teaching hospitals in Thi-Qar/Iraq, for the period from June 1st, 2022 to February 27th, 2023. Non- probability, purposive sample of 41 nurses were selected for the purpose of the study. An instruction program and a questionnaire were constructed for the purpose of the study. Content validity of the program and the questionnaire are determined through panel of experts in adult health nursing and respiratory specialist, and internal consistency reliability is obtained through pilot study. Data are collected through the use of the questionnaire and analyzed through the application of descriptive and inferential statistical approaches which are applied by using SPSS version 23 such as frequency, percentage, mean of score, standard deviation, ANOVA and T. test. Results: The results of the present study showed that nurses who were providing care for patients with COVID-19 in the isolation unit had poor to fair knowledge about chest physiotherapy techniques, and their knowledge was not affected by their demographic characteristics. Conclusions: The study concluded that nurses working at the isolation units need to be more knowledgeable on chest physiotherapy techniques provided for patients with COVID-19. Recommendations: The current constructed instruction program is essential to raise nurses’ knowledge and skills about chest physiotherapy techniques for patients with COVID-19.